Mut’ah Marriage in the Sunni-Shi'i School from the Perspective of Maqasid al-Shariah - Sani, Abubakar Muhammad; Gumel, Salisu Muhammad (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study examines the jurisprudential status of mut’ah marriage within Sunni and Shiʿi legal traditions from the perspective of maqasid al-shariʿah. The research employs a comparative doctrinal legal methodology with a qualitative approach through the analysis of primary Islamic legal sources, including the Qurʾan, hadith, classical juristic treatises, and literature on usul al-fiqh. The maqasid-based ethical analysis was also applied in this study to evaluate the implications of temporary marriage on the protection of lineage, human dignity, and social order. The findings reveal that Sunni jurisprudence generally considers mut’ah a prohibited practice based on the doctrine of naskh and the claimed ijmaʿ of classical jurists, whereas Shiʿi jurisprudence maintains its permissibility based on the continuing validity of Qurʾan 4:24 and differing interpretations of prophetic traditions. Despite these doctrinal differences, the study demonstrates that both schools attempt to justify their positions through broader objectives of Islamic law, particularly the protection of family structure and moral order. The study concludes that maqasid al-shariʿah provides an important analytical framework for understanding how Islamic legal traditions negotiate textual authority, ethical considerations, and social realities within Islamic family law. By integrating doctrinal, ethical, and socio-legal perspectives within comparative Islamic jurisprudence, this research contributes to contemporary Islamic legal discourse through a cross-sectarian and maqasid-oriented analysis of mut’ah marriage.